Microbial fuel cells for a soil-based green energy conversion system - Kumar K.S.A.; Vardhan A.S.S.; Vardhan A.S.S.; Kumar S.; Saket R.K.; Rajendran R.; Eslamian S. (My University, 2025)
This paper presents technological aspects, operating principle and scientific applications of microbial fuel cells (MFCs) for a soil-based green energy conversion system. MFC provides a likely low cost, a highly efficient and renewable energy-producing alternative to conventional energy resources. Only a few biosensors MFC have been used practically, providing current for low power devices. To further improve the MFC technology, an understanding of the limitations and microbiology of these systems are required. Some researchers are uncovering that the importance of the MFC technology is not only the production of electricity but the ability of electrode associated microbes to degrade wastes and toxic chemicals. This paper provides a platform to explore the possibilities of generating renewable power using biomass and the working principle of the MFC technology with its applications. The soil microbial fuel cell (SMFC) technology is also implemented in the soil for green electricity generation. Copyright © 2021 Inderscience Enterprises Ltd.